Questionnaire-based analysis of autism spectrum disorders and gastrointestinal symptoms in children and adolescents: a systematic review and meta-analysis - Gan, Huizhong; Su, Yanhong; Zhang, Linlin; Huang, Guolin; Lai, Ciai; Lv, Ying; Li, Yongchun (Frontiers in Pediatrics, 2023)
Abstract Background: Gastrointestinal (GI) symptoms are frequently experienced by children with autism spectrum disorder (ASD), and these symptoms cause difficulties for these children and their families. However, studies of GI symptom prevalence differ significantly. This meta-analysis aimed to analyze the prevalence of GI symptoms in children with ASD. Methods and Findings: PubMed, Scopus, Web of Science, EMBASE were electronically searched to collect all literature on gastrointestinal symptoms of children with ASD collected through questionnaires or scales from January 2012 to May 2021. Four researchers independently scanned the literature and extracted information on general characteristics. First author name, year of publication, geographical location, type of study, sample sizes of ASD and control (if any) children, sex and average age, number of GI cases, number of GI symptoms, GI assessment tools (gastrointestinal symptoms scale), autism diagnosis methods, and other necessary data were collected and analyzed using Stata V16. The questionnaires included the Rome, 6-GSI, GIQ、GSRS、GSIQ、ADI-R、PedsQL-GI, parent-report, GI-related, and self-administered questionnaires. Compared with typically developing (TD) children, the odds ratio for In children with ASD with at least one GI symptom was 3.64, and the total prevalence was 55%. The cumulative prevalence rates of various symptoms were summarized, showing that 37% of children with ASD had constipation, 21% had abdominal pain, 19% had diarrhea, 8% had vomiting, and 23% had abdominal distension. Conclusions: The results of this meta-analysis on GI symptoms in ASD show that patients with ASD are more likely to develop symptoms than TD children. The prevalence of GI symptoms in In children with ASD was 55%.